2020
DOI: 10.1111/acer.14445
|View full text |Cite
|
Sign up to set email alerts
|

SLC Neurotransmitter Transporters as Therapeutic Targets for Alcohol Use Disorder: A Narrative Review

Abstract: Alcohol use disorder (AUD) is 1 of the most prevalent of all substance use disorders and contributes significantly to global disease burden. Despite its prevalence, <10% of individuals with AUD receive treatment. A significant barrier to receiving treatment is a lack of effective pharmacotherapies. While 3 medications have been approved by the FDA for AUD (disulfiram, acamprosate, naltrexone), their efficacy remains low. Furthermore, a number of undesirable side effects associated with these drugs further redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Inhibitory and excitatory neurotransmitters in the brain balance neurochemicals. 6,7,9 Neurotransmitters initiate and transmit nerve conduction through the nervous system; alcohol consumption affects each one. 6,7,9 Thiamine (vitamin B-1) is a cofactor for synthesizing neurotransmitters, enhancing neuronal function, and converting carbohydrates into energy.…”
Section: Neurotransmittersmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibitory and excitatory neurotransmitters in the brain balance neurochemicals. 6,7,9 Neurotransmitters initiate and transmit nerve conduction through the nervous system; alcohol consumption affects each one. 6,7,9 Thiamine (vitamin B-1) is a cofactor for synthesizing neurotransmitters, enhancing neuronal function, and converting carbohydrates into energy.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…6,7,9 Neurotransmitters initiate and transmit nerve conduction through the nervous system; alcohol consumption affects each one. 6,7,9 Thiamine (vitamin B-1) is a cofactor for synthesizing neurotransmitters, enhancing neuronal function, and converting carbohydrates into energy. 10,11 Thiamine is not manufactured in the body and must be acquired from the diet.…”
Section: Neurotransmittersmentioning
confidence: 99%
See 1 more Smart Citation
“… 75 The neurotransmitters linked to reinforcing effects of alcohol are said to be endogenous opiates, GABA, serotonin, dopamine, and glutamate acting on NDMA receptors. 76 There have been numerous studies that found chronic ethanol exposure increases expression of NMDARs in the hippocampus; 77 , 78 medial orbitofrontal cortex; 77 agranular insular cortex; 79 nucleus accumbens core; central nucleus of amygdala; 80 and other parts of the central nervous system. 81 It is important to note this compensatory mechanism has been shown to proliferate NMDARs that deviate from the endogenous receptors.…”
Section: Introductionmentioning
confidence: 99%